MECHANISMS IN THE INHIBITION OF MICROORGANISMS BY SORBIC ACID - York, George K. (1964)
York, George K. (University of California, Davis), and Reese H. Vaughn. Mechanisms in the inhibition of microorganisms by sorbic acid. J. Bacteriol. 88:411–417. 1964.—Oxidative assimilation of glucose, acetate, succinate, and fumarate by washed cells of Escherichia coli, Pseudomonas aeruginosa, and Saccharomyces cerevisiae was inhibited by concentrations of sorbic acid ranging from 15 to 105 mg per 100 ml. At higher concentrations, the oxidation of these substrates was inhibited. Oxidative phosphorylation by submicroscopic particles of E. coli was reduced by about 30% by 37 mg per 100 ml of sorbic acid. The sulfhydryl enzymes fumarase, aspartase, and succinic dehydrogenase were inhibited by sorbic acid. The loss of activity of sorbic acid after reacting with cysteine suggested that a thiol addition occurred, which is believed to be the mechanism of action against sulfhydryl enzymes or cofactors.